2012
DOI: 10.2139/ssrn.2131468
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Tax Salience and Gasoline Demand

Abstract: We demonstrate that the carbon tax imposed by the Canadian province of British Columbia, a unique carbon pricing policy that comprehensively applies to all fossil fuels, caused a decline in short-run gasoline demand that is significantly greater than would be expected from an equivalent increase in the market price of gasoline. That the carbon tax is more salient, or yields a larger change in demand than equivalent market price movements, is robust to a range of specifications including intuitively plausible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
(28 reference statements)
2
12
0
Order By: Relevance
“…This is consistent with a body of literature indicating that there may a higher responsiveness of consumer behaviour to taxor other policy-induced price changes than normal market-price fluctuations, due to a "salience" or "signaling" effect (see: Rivers and Schaufele, 2012;Li, Linn and Muehlegger, 2012;Sunstein and Taylor, 2008). The resulting uncertainty underlines the risks in predicting the take-up and cost of tax subsidies.…”
Section: Box 3 the Challenge Of Tax Expenditure Cost Controlsupporting
confidence: 90%
“…This is consistent with a body of literature indicating that there may a higher responsiveness of consumer behaviour to taxor other policy-induced price changes than normal market-price fluctuations, due to a "salience" or "signaling" effect (see: Rivers and Schaufele, 2012;Li, Linn and Muehlegger, 2012;Sunstein and Taylor, 2008). The resulting uncertainty underlines the risks in predicting the take-up and cost of tax subsidies.…”
Section: Box 3 the Challenge Of Tax Expenditure Cost Controlsupporting
confidence: 90%
“…In British Columbia, the levy in 2008 of a carbon tax gradually increased to 30 CAN $/tCO 2 eq (corresponding to an increase of roughly 0.07 CAN $ per liter of gasoline) was accompanied by a 18.8% reduction of per capita consumption of fuels subject to the tax compared to the rest of Canada (Elgie and McClay 2013). Rivers and Schaufele (2012) showed that this reduction is 4.9 times greater than that expected from an equivalent increase in just the price of fuel (as opposed to a fuel tax). This is likely related to the fact that the provision of environmental information to consumers reduces their willingness to pay for the most polluting products (Michaud et al 2017;Ji et al 2017).…”
Section: Effectiveness Of the Price Changesmentioning
confidence: 90%
“…4 In the context of gasoline consumption, recent studies including Davis and Kilian (2011), Barandini and Weber (2012), Rivers and Schaufele (2012), and Scott (2012) all provide evidence that consumer respond to gasoline taxes differently from other components. Barandini and Weber (2012) examine gasoline demand in Switzerland using time-series data.…”
mentioning
confidence: 99%
“…Barandini and Weber (2012) examine gasoline demand in Switzerland using time-series data. Rivers and Schaufele (2012) use province-level panel data to investigate the consumer response to a carbon tax on fossil fuels in British Columbia, Canada. Finally, Davis and Kilian (2011) and Scott (2012) both employ U.S. state-level panel data on gasoline consumption from 1989 to 2009.…”
mentioning
confidence: 99%
See 1 more Smart Citation